2016
DOI: 10.17795/zjrms-7939
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Aloe Vera on Superovulated Oocytes and Folliculogenesis in Diabetic Mice

Abstract: Background: Reproductive problems such as impaired folliculogenesis and anovulation are observed in diabetic women.Material and Methods: Objectives: In this study the protective effects of Aloe vera (a traditional herb) on oocytes and ovarian folliculogenesis, were investigated. Methods: For this purpose 25 mice were divided in five groups: control, Aloevera trated mice, insulin treated and aloe vera treated diabetics and diabetics. Diabetes were induced by a single injection of stereptozotocin (190 mg/kg, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous research on STZ-induced diabetic models suggests that the size of oocytes in the antral follicle is less than other nondiabetic groups (4). Also, Afrough and colleagues reported that diabetes causes a delay in the arrival of oocyte into metaphase II and decreases oocyte diameter and increases the perivitelline space (25). The results further show that the ratio of the diameter of the nucleus to the ooplasm increases significantly in the metformintreated compared to the STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 87%
“…Previous research on STZ-induced diabetic models suggests that the size of oocytes in the antral follicle is less than other nondiabetic groups (4). Also, Afrough and colleagues reported that diabetes causes a delay in the arrival of oocyte into metaphase II and decreases oocyte diameter and increases the perivitelline space (25). The results further show that the ratio of the diameter of the nucleus to the ooplasm increases significantly in the metformintreated compared to the STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 87%
“…Whereas aloe vera improves the follicular development and ovulation in diabetic mice by defending against the damages of oxidative stress. 21 The graafian follicles of experimental group B showed decreased size, vacuolization and atrophy of the oocyte. The current research revealed that the mean diameter of graafian follicle in all groups was statistically significant (p-value = 0.004).…”
Section: Discussionmentioning
confidence: 92%